Vasomotor symptoms in menopause – diagnostic and treatment - Sobstyl, Małgorzata; Bednarek, Wiesława; Tkaczuk-Włach, Joanna; Sobstyl, Jacek; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2011)
Hot flashes and night sweats are common menopausal symptoms, which influence greatly the quality of women’s lives, often by eliminating them from professional or everyday lives. Etiopathogenesis of symptoms has not been fully explained. A great role is attributed to sudden decrease of estrogens, disorders of neurotransmitters and neuromodulators activity such as noradrenalin, dopamine, serotonin and thermoregulation disorders. Estrogen and estrogen-progestogen therapy is recommended as the most effective treatment for vasomotor symptoms. Yet, more and more consideration should be given to selective inhibitors of serotonin and noradrenalin, gabapentin.